please solve fast 1
Attachments:
![](https://hi-static.z-dn.net/files/db6/0b3b2ba9f58116444a966c8c18f13cd4.jpg)
Answers
Answered by
1
Answer:
Hope this answer will help you
Attachments:
![](https://hi-static.z-dn.net/files/db9/a7db868f1258b9f8d567435770f30fa7.jpg)
Answered by
0
Answer:
17. 2) (√3+√2)².
It is in the form of (a+b)²=a²+2ab+b².
Where a=√3 & b=√2.
(√3+√2)²=(√3)²+2(√3)(√2)+(√2)².
=3+2√6+2. (Because √3×√2=√6).
=5+2√6.
Sorry I understood only 1 question.
I think this is your answer.
Similar questions